2006
DOI: 10.1073/pnas.0508121103
|View full text |Cite
|
Sign up to set email alerts
|

Conserved thermodynamic contributions of backbone hydrogen bonds in a protein fold

Abstract: Backbone-backbone hydrogen-bonding interactions are a ubiquitous and highly conserved structural feature of proteins that adopt the same fold (i.e., have the same overall backbone topology). This work addresses the question of whether or not this structural conservation is also reflected as a thermodynamic conservation. Reported here is a comparative thermodynamic analysis of backbone hydrogen bonds in two proteins that adopt the same fold but are unrelated at the primary amino acid sequence level. With amide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 30 publications
1
35
0
1
Order By: Relevance
“…It has been shown that electrostatic screening is the main reason for the distinct backbone conformational preferences of amino acid residues in peptides and proteins (53), the nearest neighbor effect (54), and the formation of transient β-strands in unfolded proteins (55). It has also been shown, using amide to ester mutations, that H bonds in the protein interior are stronger than those exposed to solvent (56)(57)(58).…”
Section: Ir Spectroscopy Of Water Molecules In the Neighborhood Of Pumentioning
confidence: 99%
“…It has been shown that electrostatic screening is the main reason for the distinct backbone conformational preferences of amino acid residues in peptides and proteins (53), the nearest neighbor effect (54), and the formation of transient β-strands in unfolded proteins (55). It has also been shown, using amide to ester mutations, that H bonds in the protein interior are stronger than those exposed to solvent (56)(57)(58).…”
Section: Ir Spectroscopy Of Water Molecules In the Neighborhood Of Pumentioning
confidence: 99%
“…6,7 In this context, the computational approach must be specially highlighted, [8][9][10][11] as it can analyze this interaction individually, without considering the rest of energetic contributions ͑hydrophobicity, electrostatics, etc.͒.…”
Section: Introductionmentioning
confidence: 99%
“…In vorausgegangenen Studien wurden hauptsächlich monomere a-Helices, [7][8][9][10] b-Faltblätter [11,12] oder komplexe Proteine [13][14][15][16] Das a-helicale Coiled-Coil-Strukturmotiv ist gut charakterisiert und in der Natur weit verbreitet. Es besteht aus mehreren a-Helices, die eine superhelicale Quartärstruktur bilden.…”
unclassified